Ladder of angels : scenes from the Bible - L'Engle, Madeleine (New York, N.Y. : Penguin Books, 1980)
Presents stories and scenes from the Old Testament rewritten by the author and accompanied by children's paintings.
Keywords: Bible -- Meditations; Bible -- Illustrations; Bible stories -- O. T; Children's art